Vertical bargaining and obfuscation - Edona Reshidi (Bank of Canada, 2022)
Manufacturers often engage in practices that impede consumer search. Examples include proliferating product varieties, imposing vertical informational restraints, and banning online sales to make it more difficult for consumers to compare prices. This paper models vertical bargaining over wholesale prices and obfuscation levels and finds that obfuscation arises in equilibrium whenever retailers have some bargaining power. Once the bargaining power rests with the manufacturer, the equilibrium involves no obfuscation. The final consumers, however, are worse off compared with settings when retailers have all the bargaining power. We show that in vertical markets, policies that impose caps on obfuscation may induce higher wholesale and retail prices. Instead, we propose caps on wholesale prices as an effective consumer protection policy.
Keywords: C70; L42; L13; 330; Economic models; Market structure and pricing